Strategi Pengembangan Ekowisata Mangrove dalam Meningkatkan Ekonomi Masyarakat di Bukit Batu, Kabupaten Bengkalis - Eka Desnyarti; Zulkarnaini Zulkarnaini (Badan Penerbit STIEPARI Press, 2025)
Mangrove ecotourism is a natural tourism potential that holds significant economic and conservation values. This study aims to identify effective strategies for developing mangrove ecotourism to enhance the local community’s economy in Bukit Batu, Bengkalis Regency. The research employs a qualitative approach with data collection techniques including interviews, observations, and document studies. Data analysis is conducted using descriptive analytical methods to examine the potentials, challenges, and opportunities in mangrove ecotourism development. The results reveal that mangrove ecotourism development can increase community income through higher tourist visits, community involvement in management, and the development of tourism products based on local culture and environment. However, challenges such as limited supporting facilities, lack of human resource training, and conservation awareness need to be addressed. Recommended development strategies include improving infrastructure, empowering the community through training and education, and promoting sustainable tourism. With the implementation of these strategies, it is expected that mangrove ecotourism in Bukit Batu will thrive and provide significant economic benefits to the local community.